'Beanz Meanz Professional Learning': Beginning a Pedagogical Reflective Sketchbook. (1st September 2020) - Hall, Emese
I was attempting to write a traditional text-based article defining what I have come to term a 'Pedagogical Reflective Sketchbook'. The aim was to consider what insights might be gained from existing research on teachers' use of reflective sketchbooks – and similarly named books – for their professional learning, leading to my definition of a Pedagogical Reflective Sketchbook. However, I told myself (aloud) 'I can't say what I want to say in words'. Although not a totally surprising revelation, it was a call to action. I, therefore, began to develop my own visual musings centred on the analogy of being like a Michelin-starred chef serving baked beans on toast – a pedagogical frustration in my current academic role. In order to better understand a Pedagogical Reflective Sketchbook, it made perfect sense to begin one, in keeping with the spirit of my research intentions. This visual essay explains more…